Microfluidic solvent extraction of rare earth elements from a mixed oxide concentrate leach solution using Cyanex® 572. (12th July 2016) - Kolar, Elisabeth; Catthoor, Rik P.R.; Kriel, Frederik H.; Sedev, Rossen; Middlemas, Scott; Klier, Eric; Hatch, Gareth; Priest, Craig
Abstract: Solvent extraction of rare earth elements (REEs) involves hundreds of individual extraction and phase separation cycles, fine adjustment of solution conditions, and individual stage and overall process times that are long. Therefore, we investigated microfluidic solvent extraction (microSX) of REEs from a leached mixed rare earth oxide (REO) mineral concentrate using a phosphorus-based cationic exchange extractant (Cyanex® 572). A Y–Y microchip was used, in which the aqueous and organic phases were contacted for up to 15 s with sub-second resolution. The extraction rate and selectivity for heavy REEs was determined for the prepared leach solution. Good selectivity for heavy REEs was observed using the microchip for leach solutions adjusted to pH 0.7. Extraction rates on the microchip were typically double that observed in conventional (bulk) solvent extractions, except for Lu and Yb, which were three-times faster. The faster extraction can be largely attributed to the higher surface-to-volume ratio achieved in our microfluidic experiments; double that observed for bulk extractions under the conditions employed. Graphical abstract: Highlights: Solvent extraction of REEs from leach solutions is performed on a microfluidic chip. Leach solutions were derived from industrial grade mixed rare earth oxide ore. Extraction rates are 2–3 times higher in microfluidic extraction. Good selectivity for heavy REEs was found for leach solutions adjusted to pH=0.7.